The Effectiveness of Vitamin C on Iron Absorption in Adult and Young Women - Soeka, Luh Made Anindita Adristi; Prabawa, Aditya; Meilani, Ni Komang Putri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Anemia is a common health problem among women, particularly adolescents, due to increased physiological demands.According to WHO data, the prevalence of anemia in Indonesia in 2024 was 34.2% with a target prevalence of 13.1%. Given this issue, the purpose of this study was to find out how effective vitamin C is in iron absorption to reduce anemia rates. The method used in writing this article is a Narrative Literature Review based on searches conducted through Google Scholar, PubMed, and SageJournal for articles published between 2015–2025. Nine studies that met inclusion and exclusion criteria using the PRISMA approach were analyzed narratively.From the resultsof the study, there is variation in the number of doses used in experimental and quasi-experimental studies. This review also considers studies involving iron stores, such as serum ferritin, to compare with hemoglobin analysis, which is often overlooked. Overall, the evidence indicates that vitamin C supports iron absorption and contributes to improved hemoglobin status. The effect is observed consistently across various study designs. For this reason, every woman should make sure to gets enough vitamin C, which is essential for improving iron absorption.